Numerical Analysis of the Effect of Heterogeneity on Underground Roadway Stability under Dynamic Loads - Tao Guo; Hao Feng; Zequan Sun; Yang Zhao; Xingyu Wu; Xinggang Xu; Lishuai Jiang (Shock and Vibration)
With the increasing depth of coal mining and expanding mining scale, the rocks surrounding deep roadways are in a complex mechanical condition of frequent dynamic disturbance. The heterogeneity has an important influence on rock mass failure under dynamic loads. Therefore, it is necessary to study the deformation and failure of heterogeneous roadway under dynamic load. In this paper, the effect of heterogeneity on stability of roadway under static and different dynamic loads is studied. According to the results, the effect of rock mass heterogeneity on the deformation and failure of surrounding rock varies with different degrees of heterogeneity. Under static loading conditions, the stability of roadway is negatively correlated with the degree of heterogeneity of the rock mass. Under dynamic loading conditions, the change of heterogeneity degree has significant influence on the stability of surrounding rock. With the increase in dynamic load strength, the change in variation difference in the average value of roof sag, stress distribution, and plastic zone caused by variations in heterogeneity will increase. This study contributes to understanding the deformation and failure characteristics of heterogeneous roadways under dynamic loads and can be used to analyze heterogeneous roadways under dynamic loads.